PELATIHAN DIGITAL STORYTELLING BERBASIS KOLABORASI BAGI MAHASISWA SEMESTER III PROGRAM STUDI PENDIDIKAN BAHASA INGGRIS UNIVERSITAS 17 AGUSTUS 1945 BANYUWANGI - Rahman, Abd.; Novitasari, Devi (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
Crafting digital storytelling involves a sequence of 12 steps. These phases demonstrate the intricate nature of crafting digital narratives. Furthermore, the third-year students of the English Language Education program at the University of 17 Agustus 1945 Banyuwangi lack familiarity with these steps the features in the software and how to use these features in creating digital storytelling. In response to these problems, this training aims to train participants to develop digital storytelling collaboratively to exchange experiences and expertise to generate more innovative digital stories. 30 students (23 women and 7 men) attended this training, which lasted 6 weeks. This training comprises three primary stages: before crafting digital storytelling, preparation of equipment, crafting digital storytelling, and after crafting digital storytelling. Drawing from the assessment of digital stories created by participants and questionnaires, collaborative digital storytelling training allows students to build knowledge about digital technology literacy and understanding of stories. This digital storytelling training also significantly affects their speaking skills, which can be seen from several aspects such as pronunciation, vocabulary, grammar, fluency and self-confidence. This collaborative digital storytelling training explicitly shows that students can handle complexity or challenges while creating digital storytelling because they can share knowledge and have a high level of responsibility for the same goal, which is creating more creative and inspiring digital stories.